KONTEN DIGITAL UMKM TAHU SAMBAL MBAK JIAH MELALUI TIK-TOK PADA AKUN @INFOMAKANSOLO UNTUK MENINGKATKAN PENJUALAN PASCA PANDEMI COVID-19 - Rendi Irawan, Andrean; Hindra H, Nurnawati; Widyowati, Estu (Solidaritas, 2024)
This research discusses the Marketing Strategy of the Tiktok Application as an onlinepromotional media at Tahu Sambal Mbak Jiah, where these stalls utilize each other oruse the Tiktok Application as their promotional media and sell food at very affordableand unique prices. to get customers. Mbak Jiah's chili tofu offers a different concept andis new to this city. This research aims to find out about: First, the marketing strategy inusing the Tiktok application as an online promotional media for Ms. Jiah's TahuSambal. Second, marketing strategies in using the Tiktok application during thepandemic. This research is field research using descriptive qualitative researchmethods. Data collection techniques using observation, interviews and documentation.The data validation technique uses source triangulation by collecting similar data andinformation from various.Keywords: TikTok application, marketing strategy, Mbak Jiah's Sambal Tofu